IMPLIKATUR PERCAKAPAN MENGAJAK DALAM LINGKUNGAN MASYARAKAT MELAYU SAROLANGUN - Bambang Prastio; Mujiyono Wiryotinoyo; Harry Soedarto (Puitika, 2019)
This study aims to describe verbal expressions and speech functions in the form of verbal conversation implicature in invite Sarolangun Malay society. Pragmatic analysis is used to analyze data. Related to the results of this study indicate that there are nine conversation implicatures inviting. First, there are four verbal forms and declarative speech functions. Second, there are four verbal forms and interrogative speech functions. Third, there is one verbal form and an imperative speech function. The results of this study are expected to be a consideration for subsequent research and serve as a consideration for someone to communicate indirect. Keywords: conversation implicature, invate, malay